Two Years of Obscure Gastrointestinal Bleeding: Lessons from a Diagnostic Odyssey (Journal of Society of Surgeons of Nepal, 2025)
Lower GI bleeding presents as hematochezia and is more common in old age and less common in young adults and children. Fresh bleeding is more commonly associated with benign anal disorders like fissure and hemorrhoids, but melena is more commonly associated with upper gastrointestinal bleeding with cancerous growth in the elderly. However rare, melena can also be seen in proximal lower gastrointestinal bleeding (mainly proximal jejunum), and it does occur in young adults due to non-cancerous causes.We report a case of a 26-year-old male, requiring frequent blood transfusions for 2 years in different institutions of Nepal due to GI bleeding in the form of melena. He underwent a series of investigations and acute treatment at different centers for this problem. No definitive cause was identified during this period, and the patient later had to undergo surgical management for massive bleeding requiring multiple transfusions at our institute.This case report is to emphasize the need for the use of more aggressive and advanced investigative tools for the identification of bleeding spots in the gastrointestinal tract, which otherwise would not have been picked up by usual investigative tools.  We should think out of the box to diagnose and manage this kind of patient successfully.